2021
DOI: 10.3390/biom11081084
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Roles and Clinical Usefulness of Periostin in Type 2 Inflammation and Pulmonary Fibrosis

Abstract: Periostin is known to be a useful biomarker for various diseases. In this article, we focus on allergic diseases and pulmonary fibrosis, for which we and others are now developing detection systems for periostin as a biomarker. Biomarker-based precision medicine in the management of type 2 inflammation and fibrotic diseases since heterogeneity is of utmost importance. Periostin expression is induced by type 2 cytokines (interleukin-4/-13) or transforming growth factor-β, and plays a vital role in the pathogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 195 publications
0
9
0
Order By: Relevance
“…[15][16][17] In particular, periostin was provided to be expressed in allergy, inflammation, fibrosis, and tumors for its promotive role in intermolecular interactions. 18,19 It has been reported that some of its activities were mediated by its binding to cell surface receptors of the integrin family. 19,20 The enhanced secretory function of heart proximal infarction area ensures the timeliness of fibrous repair and effectively prevents the occurrence of cardiac rupture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] In particular, periostin was provided to be expressed in allergy, inflammation, fibrosis, and tumors for its promotive role in intermolecular interactions. 18,19 It has been reported that some of its activities were mediated by its binding to cell surface receptors of the integrin family. 19,20 The enhanced secretory function of heart proximal infarction area ensures the timeliness of fibrous repair and effectively prevents the occurrence of cardiac rupture.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 It has been reported that some of its activities were mediated by its binding to cell surface receptors of the integrin family. 19,20 The enhanced secretory function of heart proximal infarction area ensures the timeliness of fibrous repair and effectively prevents the occurrence of cardiac rupture. In our study, the periostin levels were elevated post-MI in the apex of the heart proximal infarction area, which suggested that the ECM in proximal infarct tissue played an important role in myocardial fibrosis post-MI.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9, TIMP-1, periostin and TGF-β1 are known to contribute to airways remodelling. [20][21][22][23] When compared between the present BDR and absent BDR groups, significantly higher levels of serum MMP-9 (507.8 ± 259.5 vs. 352.2 ± 240.9 ng/mL, p = .019) and MPO (560.9 ± 234.0 vs. 412.3 ± 242.8 ng/mL, p = .022) were noted (Table 2); however, no significant differences were noted in serum predicted the present BDR group from the absent BDR group (area under the curve [AUC] = 0.740, p = 0.004, Figure 1D).…”
Section: Comparison Of Serum Biomarkersmentioning
confidence: 99%
“…Dermal periostin is upregulated in patients with both AD and prurigo nodularis (PN, a chronic, inflammatory skin condition characterized by itchy nodules), and also induces allergic itch in mice, dogs and non-human primates via integrin α V β 3 ( Kou et al, 2014 ; Sung et al, 2017 ; Mishra et al, 2020 ; Hashimoto et al, 2021c ). Through perturbed periostin homeostasis, fibroblasts could therefore play a key role in pruritus pathology ( Hashimoto et al, 2021a ; Ono et al, 2021 ).…”
Section: Cell Types and Receptors Involved In Itchmentioning
confidence: 99%